Role of access charges in the migration from copper to FTTH - François Jeanjean; Julienne Liang (International Telecommunications Society (ITS), 2011)
We consider a horizontally and vertically differentiated duopoly model in order to analyze both intra- and inter-platform competition in an always corvered broadband access market (Copper-Copper, Copper-FTTH and FTTH-FTTH competitions). The model is purely static and does not address dynamic efficiency issues. It shows that the access charges play a significant role in the migration from copper to FTTH and in FTTH investment incentives, provided that consumers are segmented. In FTTH-infrastructure-based competition, investment incentives tend to increase with the copper access charge, while in FTTH-servicebased competition, FTTH investment incentives are much more sensitive to the FTTH access charge than to the copper access charge. A comparison of FTTH-infrastructure-based and FTTH-service-based competition in terms of nationwide FTTH coverage and social welfare indicates that FTTH-infrastructure-based competition leads to a higher level of nationwide FTTH coverage and social welfare.
Keywords: 330